Sensitization of C-fiber nociceptors in mice with sickle cell disease is decreased by local inhibition of anandamide hydrolysis. Issue 9 (September 2017) - Uhelski, Megan L.; Gupta, Kalpna; Simone, Donald A.
Abstract : Abstract: Chronic pain and hyperalgesia, as well as pain resulting from episodes of vaso-occlusion, are characteristic features of sickle cell disease (SCD) and are difficult to treat. Since there is growing evidence that increasing local levels of endocannabinoids can decrease hyperalgesia, we examined the effects of URB597, a fatty acid amide hydrolase (FAAH) inhibitor, which blocks the hydrolysis of the endogenous cannabinoid anandamide, on hyperalgesia and sensitization of cutaneous nociceptors in a humanized mouse model of SCD. Using homozygous HbSS-BERK sickle mice, we determined the effects of URB597 on mechanical hyperalgesia and on sensitization of C-fiber nociceptors in vivo. Intraplantar administration of URB597 (10 μg in 10 μL) decreased the frequency of withdrawal responses evoked by a von Frey monofilament (3.9 mN bending force) applied to the plantar hind paw. This was blocked by the CB1 receptor antagonist AM281 but not by the CB2 receptor antagonist AM630. Also, URB597 decreased hyperalgesia in HbSS-BERK/CB2R −/− sickle mice, further confirming the role of CB1 receptors in the effects produced by URB597. Electrophysiological recordings were made from primary afferent fibers of the tibial nerve in anesthetized mice. The proportion of Aδ- and C-fiber nociceptors that exhibited spontaneous activity and responses of C-fibers to mechanical and thermal stimuli were greater in HbSS-BERK sickle mice as compared to control HbAA-BERK mice. Spontaneous activity and evoked responses of nociceptors were decreased by URB597 via CB1 receptors. It is suggested that enhanced endocannabinoid activity in the periphery may be beneficial in alleviating chronic pain associated with SCD. Abstract : In a murine model of sickle cell disease, hyperalgesia and sensitization of cutaneous nociceptors were decreased by the injection of the FAAH inhibitor URB597.